2018
DOI: 10.26434/chemrxiv.7447877.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vapor-phase Stabilization of Biomass Pyrolysis Vapors Using Mixed-metal Oxide Catalysts

Abstract: <div>Mixed-metal oxides possess a wide range of tunability and show promise for catalytic stabilization of biomass pyrolysis products. For materials derived from layered double hydroxides, understanding the effect of divalent cation species and divalent/trivalent cation stoichiometric ratio on catalytic behavior is critical to their successful implementation. In this study, four mixed-metal oxide catalysts consisting of Al, Zn, and Mg in different stoichiometric ratios were synthesized and tested for ex-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…74,75 The catalytic reactions occurring in CFP include dehydration, decarbonylation, decarboxylation, ketonization, aldol condensation, aromatization, hydrodeoxygenation, hydrogenation, and cracking. 74,75 Catalysts applied in both in situ and ex situ CFP include zeolites (for example, ZSM-5) and acid-functionalized mesoporous materials (for example, MCM-41), 19,44,74,76 acidic metal oxides (for example, Al 2 O 3 , TiO 2 , and ZrO 2 ), 77−80 basic metal oxides (for example, MgO and CaO), 81−83 and mixedmetal oxides with both acidic and basic sites (for example, MgO/ZnO with Al 2 O 3 , 83 and Mn 2 O 3 /ZrO 2 with CeO 2 84 ). In addition, supported noble metal bifunctional catalysts (for example, Pt/TiO 2 85 and Ru/TiO 2 86 ) together with H 2 are used in ex situ CFP for hydrodeoxygenation of the pyrolysis vapor.…”
Section: Introductionmentioning
confidence: 99%
“…74,75 The catalytic reactions occurring in CFP include dehydration, decarbonylation, decarboxylation, ketonization, aldol condensation, aromatization, hydrodeoxygenation, hydrogenation, and cracking. 74,75 Catalysts applied in both in situ and ex situ CFP include zeolites (for example, ZSM-5) and acid-functionalized mesoporous materials (for example, MCM-41), 19,44,74,76 acidic metal oxides (for example, Al 2 O 3 , TiO 2 , and ZrO 2 ), 77−80 basic metal oxides (for example, MgO and CaO), 81−83 and mixedmetal oxides with both acidic and basic sites (for example, MgO/ZnO with Al 2 O 3 , 83 and Mn 2 O 3 /ZrO 2 with CeO 2 84 ). In addition, supported noble metal bifunctional catalysts (for example, Pt/TiO 2 85 and Ru/TiO 2 86 ) together with H 2 are used in ex situ CFP for hydrodeoxygenation of the pyrolysis vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Other than CaO and ZnO, CuO, Fe 2 O 3 , 13 TiO 2 , ZrO 2 , 14 NiO, MgO, 15 and Al 2 O 3 16 have been examined for use in the catalytic biomass pyrolysis. Edmunds et al showed that a Mg‐Al oxide catalyst was effective at upgrading the pyrolysis vapor evolved from biomass feedstock (eg, pine wood), which led to high toluene and xylene yields 17 …”
Section: Introductionmentioning
confidence: 99%
“…Edmunds et al showed that a Mg-Al oxide catalyst was effective at upgrading the pyrolysis vapor evolved from biomass feedstock (eg, pine wood), which led to high toluene and xylene yields. 17 Beyond biomass conversion, metal oxides have recently attracted interest in plastic waste treatment catalysts. For example, red mud (a mixture of a variety of metal oxides) was employed in the catalytic pyrolysis of different plastics.…”
Section: Introductionmentioning
confidence: 99%
“…A partir da pirólise de HDLs intercalados com espécies orgânicas, a estrutura e propriedades dos compostos obtidos depende de parâmetros como: (i) atmosfera (inerte, oxidante, redutora, estática, dinâmica); (ii) temperatura e taxas de aquecimento e de resfriamento; (iii) composição do HDL (variabilidade no número de oxidação dos cátions metálicos); e (iv) propriedades da espécie confinada (natureza química, estabilidade térmica). 55,73,74 Nesse sentido, poucos estudos sistematizam a variação das condições de tratamento térmico com as estruturas produzidas. Em geral, os trabalhos focam na obtenção (i) das estruturas carbonáceas, onde o HDL e estruturas derivadas atuam apenas como agente porogênico, removido após tratamento ácido; ou (ii) das nanopartículas metálicas, onde o intercalante orgânico é utilizado apenas como fonte de espécies redutoras.…”
Section: Compósitos Baseados Em Hidróxidos Duplos Lamelares E Estruturas Carbonáceasunclassified